2012
DOI: 10.1371/journal.pone.0031384
|View full text |Cite
|
Sign up to set email alerts
|

Losartan Slows Pancreatic Tumor Progression and Extends Survival of SPARC-Null Mice by Abrogating Aberrant TGFβ Activation

Abstract: Pancreatic adenocarcinoma, a desmoplastic disease, is the fourth leading cause of cancer-related death in the Western world due, in large part, to locally invasive primary tumor growth and ensuing metastasis. SPARC is a matricellular protein that governs extracellular matrix (ECM) deposition and maturation during tissue remodeling, particularly, during wound healing and tumorigenesis. In the present study, we sought to determine the mechanism by which lack of host SPARC alters the tumor microenvironment and en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
47
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 75 publications
(52 citation statements)
references
References 62 publications
4
47
0
1
Order By: Relevance
“…M2 macrophages might therefore promote tumor progression [44]. As a second possibility, Arnold and colleagues [43] speculate that the increase in local invasion could represent the response to the anti-angiogenic activity of losartan, since inhibition of angiogenesis has been shown to increase local invasion, for instance, in pancreatic cancer [45]. In the present study, we observed an increase in adhesion and invasion under in vitro conditions, i.e.…”
Section: Discussionsupporting
confidence: 59%
“…M2 macrophages might therefore promote tumor progression [44]. As a second possibility, Arnold and colleagues [43] speculate that the increase in local invasion could represent the response to the anti-angiogenic activity of losartan, since inhibition of angiogenesis has been shown to increase local invasion, for instance, in pancreatic cancer [45]. In the present study, we observed an increase in adhesion and invasion under in vitro conditions, i.e.…”
Section: Discussionsupporting
confidence: 59%
“…However, several more clinically relevant FDA/European Medicines Agency-approved drugs already exist for the identified targets, or candidate drugs are in advanced stages of clinical trials. Examples are losartan or neutralizing TGFb antibodies to target initial fibrotic processes, LOX antibodies to reduce crosslinking, and small molecules inhibiting FAK activity to correct mechanosensing in tumor cells and keratinocytes (11,31). Such drugs could be repurposed for rapid clinical implementation as prophylactic cSCC therapy in RDEB and other related, more common conditions.…”
Section: Discussionmentioning
confidence: 99%
“…The reciprocal regulation of TGF-β and SPARC has been reported in many physiological and pathological contexts (20,38,64). Recent studies reported that in Sparc -/-pancreatic tumors, aberrant TGF-β activation and high levels of TGF-β were associated with decreased pericyte recruitment, destabilization of blood vessels (42,65), vascular permeability, and inflammation contributing to tumor progression (17). Our results indicate that SPARC attenuated the cancer-stromal cell crosstalk with subsequent inhibition of the inflammatory phenotype of fibroblasts and macrophages, as demonstrated by its differential effects on activation of NF-κB and AP-1 in heterotypic cocultures.…”
Section: -Isoprostane 8-oh-dg Cytokine/growth Factor Assaysmentioning
confidence: 98%
“…Use of SPARC knockout (Sparc -/-) mice revealed that SPARC suppresses syngeneic and oncogenedriven tumors (9,(11)(12)(13)(14) through regulation of matrix deposition and through antiinflammatory, antiangiogenic, antiproliferative, and proapoptotic effects, while SPARC has been found to be upregulated in the stroma (9,15). SPARC exerts autocrine and paracrine inhibition of cancer cell proliferation through cell-cycle arrest (8,9,13,16,17) and suppression of survival signaling (7,11,12,18,19), cancer cell adhesion, and invasion (8,11,12,17,18).…”
Section: Introductionmentioning
confidence: 99%